BUILDING THE COMPETITIVENESS OF GEN ZPRENEURS THROUGH THE INTEGRATION OF A DIGITAL MINDSET, SOFT SKILLS, AND A COLLABORATIVE ECOSYSTEM - Novy Fitria (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2026)
, Mahasaraswati